Distribution of Contaminated Heavy Metals in Milk - Ocak, E. (Asian Journal of Chemistry, 2010)
Milk and most of the dairy products are also important parts of human diet. These products are likely to be exposed to heavy metals contamination. The present study determined distribution of added copper, iron and zinc to bovine milk. In different ratio of copper, iron and zinc solution was added to bovine milk and incubated. Milk samples were fractionated into fat and skim milk by centrifugation. Then, casein was separated by acid precipitation at pH 4.5 followed by centrifugation. Copper, iron and zinc concentrations in fat, casein and whey fractions were determined by atomic absorption spectrometry. Most of the copper, iron and zinc were recovered in the skim milk, average in the all of dose 76.38, 84.44 and 85.07 %, respectively whereas only 23.62, 15,56, 14.93 % of the these metals were associated to the lipid fraction. While copper, iron and zinc addition increases in milk, ratio of copper were bound casein and whey, ratio of iron were bound casein and ratio of zinc were bound to the whey increases.